Optimal Design of NGW Planet Wrench Parameter - Chen Xingqiang; He Hua; Liu Chunjing (Jixie chuandong)
Through the theoretical analysis of a three stages NGW planetary gear transmission wrench,the mathematical model with the optimal object of minimizing wrench volume is established. Under the condition of meet the constrain,the design method of mixed discrete variable method and second optimization is proposed.Through the example calculations,it shows that the method can be used to solve this kind of mixed discrete variable optimization problems in the engineering design,the optimization reliability is improved and it has some reference for structure optimization and cost controlling.